2020
DOI: 10.1038/s41586-020-2815-6
|View full text |Cite
|
Sign up to set email alerts
|

RAD51-dependent recruitment of TERRA lncRNA to telomeres through R-loops

Abstract: Telomeres which are present at the ends of eukaryotic chromosomes mediate genome stability and determine cellular lifespan 1 . Telomeric repeat containing RNAs (TERRA) are long noncoding RNAs transcribed from chromosome ends 2 , 3 , which regulate telomeric chromatin structure and telomere maintenance via telomerase and homology directed repair (HDR) 4 , 5 . The mechanisms by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
138
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(172 citation statements)
references
References 28 publications
1
138
0
Order By: Relevance
“…Here, we show that DNA:RNA hybrids involving telomeric repeats are more abundant in ALT cells compared with non-ALT cells. These results are consistent with previous reports [ 7 ], and provide a broader view on the landscape of endogenous telomeric DNA:RNA hybrids to include endogenous TTAGGG repeats, which are the most critical part of the telomeres involved in hybrid formation [ 24 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Here, we show that DNA:RNA hybrids involving telomeric repeats are more abundant in ALT cells compared with non-ALT cells. These results are consistent with previous reports [ 7 ], and provide a broader view on the landscape of endogenous telomeric DNA:RNA hybrids to include endogenous TTAGGG repeats, which are the most critical part of the telomeres involved in hybrid formation [ 24 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…TERRAs are recruited to telomeres where they form DNA-RNA hybrid R-loops. This R-loop formation regulates telomere maintenance through interactions with chromatin modifiers, telomerase, and promoting DNA repair (166,167). TERRAs also facilitate telomere replication and promote the assembly of shelterin proteins (168,169).…”
Section: Terra (Telomere Repeat-containing Rna)mentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) constitute a large fraction of the transcriptome that does not encode proteins [14], and play important roles in various biological processes, such as genome stability [15], vernalization [16], telomere maintenance [17], transcriptional activation [18], and other developmental processes [19]. Various transcriptome studies have revealed that pervasive transcription from noncoding transcripts can give rise to functional lncRNAs [20].…”
Section: Introductionmentioning
confidence: 99%